2016
DOI: 10.1089/cbr.2016.2028
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Brain Tumors with Copper-64 Chloride: Early Experience and Results

Abstract: Copper-64 chloride has favorable biological properties for brain imaging and warrants further investigation as a diagnostic tracer for GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 38 publications
(44 reference statements)
2
45
0
Order By: Relevance
“…Radioactive Cu 2+ injections are currently used in the clinic for tumor imaging . Accordingly, the administration of Cu 2+ was tested to alleviate Cu deficiency in the tissue and to enhance the anticancer activity of the formulation.…”
Section: Resultsmentioning
confidence: 99%
“…Radioactive Cu 2+ injections are currently used in the clinic for tumor imaging . Accordingly, the administration of Cu 2+ was tested to alleviate Cu deficiency in the tissue and to enhance the anticancer activity of the formulation.…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons these cancer types were chosen in the studies with [ * Cu][Cu(ATSM)] PET imaging is because of the difficulties to detect hypoxia due to the physical inaccessibility to use invasive methods [30][31][32][33]. Although the exact mechanism and relations to tissue hypoxia explaining the retention of either [ 64 [36,37], and imaging of brain tumors ([ 64 Cu]CuCl 2 ) [38]. A summary of clinical studies with either copper-labelled ATSM or ionic radiocopper is shown in Table 1.…”
Section: Clinical Studies With [ * Cu][cu(atsm)] and Ionic Copper-64mentioning
confidence: 99%
“…Cervical cancer 38 Patients were monitored through a period from 3 to 79 months. With a threshold of T/M = 3.5 the 3-year progression free and cause-specific survival rate of patients with normoxic tumors (T/M < 3.5, 71%) is significantly higher than that of hypoxic tumor (T/M > 3.5, 28%).…”
Section: Role Of Cu-64 In Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-dependent changes of brain copper fluxes in Atp7b −/− knockout WD mice was demonstrated by a longitudinal PET study using orally administered 64 CuCl 2 as a radiotracer [64]. Moreover, 64 CuCl 2 was successfully used as a radiotracer for diagnostic imaging of prostate cancer [65] and brain tumors [66] in humans with PET, based on previous use of 64 CuCl 2 as a tracer for localization of human prostate cancer xenograft tumors in rodents [67]. The findings from these studies support use of 64 CuCl 2 as a radiotracer for quantitative analysis of age-dependent changes of copper fluxes in brain aging and pathophysiology of AD with PET [6870].…”
Section: Coppermentioning
confidence: 99%